Belarus: Religious Freedom Survey, October 2020 - Glace, Olga (Occasional papers on religion in Eastern Europe, 2020)
Before the UN Human Rights Council Universal Periodic Review (UPR) of Belarus on 2 November, Forum 18 notes continuing violations of freedom of religion and belief and of interlinked freedoms of expression, association, and assembly. These have worsened amid widespread continuing protests against falsified results of the August 2020 presidential election, and against the regime's other serious violations of the human rights of the people it rules. This was originally published by Forum 18, reposted with permission. Glace, Olga (2020) "Belarus: Religious Freedom Survey, October 2020," Forum 18. Available at: http://www.forum18.org/archive.php?article_id=2612